Evolving media use in early childhood: parental motivations and their impact on child development - Coyne, Sarah M.; Almeida, Lara A. Maximiano; Shawcroft, Jane; Siddoway, Cambria; Hirschi, Talise (Frontiers in Psychology, 2026)
Media use during early childhood is common and is related to a range of both positive and negative outcomes for children. However, the motivations for why parents allow children to use media have rarely been examined, particularly over time. The current study examines the growth of four different media motivations across four years in early childhood: using media to calm children down, to educate, for enjoyment, and to keep children busy. Additionally, predictors and outcomes of the growth of media motivations were examined. Participants included 467 infants (M age = 17.77 months at the initial time point) and their caregivers. Parents completed questionnaires once a year for 4 years on their motivations for giving their children media and on child internalizing and externalizing behaviors. Using media to keep children calm was moderate at the initial time point and decreased over time. Conversely, the other three types of media motivations increased steadily over time, particularly using media because children enjoyed it. Initial levels of motivations to keep children calm and to keep children busy were both related to externalizing behaviors 4 years later. These results suggest that media motivations change over the course of early childhood and are differentially related to child behavioral outcomes over time.